2021
DOI: 10.1155/2021/2688788
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Analysis Model of the Length of Added Displaced Left-Turn Lane Based on Entropy Evaluation Method

Abstract: As the number of vehicles continues to grow in China, the problem of urban traffic congestion gets more serious, particularly at intersections. As a new type of unconventional intersection, the displaced left-turn (DLT) intersection has been widely recognized to improve the efficiency of intersections with heavy left-turn traffic flows. Converting an existing intersection into an intersection with additional DLT lanes is a valuable solution. However, the studies on DLT intersections mainly focus on performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…The emerging technology of numerical simulation has found extensive application in various disciplines. In the field of transportation, numerous studies have shown the reliable, effective, and economic advantages of using VISSIM numerical simulation [25,26]. To ensure reliability and realism, it is essential to incorporate real traffic data in the development of the simulation model and the calibration of parameters to recreate specific traffic scenarios [27].…”
Section: Introductionmentioning
confidence: 99%
“…The emerging technology of numerical simulation has found extensive application in various disciplines. In the field of transportation, numerous studies have shown the reliable, effective, and economic advantages of using VISSIM numerical simulation [25,26]. To ensure reliability and realism, it is essential to incorporate real traffic data in the development of the simulation model and the calibration of parameters to recreate specific traffic scenarios [27].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used methods include the entropy weight method, analytic hierarchy process, TOPSIS-Entropy method, and others (Vaidya and Kumar, 2006;Ding et al, 2016;Zhao et al, 2017;Shi et al, 2023). The comprehensive evaluation method has been widely applied in fields such as meteorology, architecture, ecology, and transportation (Zhao et al, 2009;Liu et al, 2017;Li et al, 2018;Wu and Hu, 2020;Pan et al, 2021). Compared with various subjective comprehensive evaluation models, the biggest advantage of the entropy weight method is that it avoids the interference of human factors on the weights of indicators, thus improving the objectivity of the comprehensive evaluation results.…”
Section: Introductionmentioning
confidence: 99%